Leadershift the 11 essential changes every leader must embrace - Maxwell, John C. (Nashville HarperCollins Leadership, 2019)
In Leadershift, John C. Maxwell helps leaders gain the ability and willingness to make leadership changes that will positively enhance their organizational and personal growth. He does this by sharing the eleven shifts he made over the course of his long and successful leadership career. Each shift changed his trajectory and set him up for new and exciting achievements, ultimately strengthening and sustaining his leadership abilities and making him the admired leadership expert he is today.
Includes bibliographical references (pages 259-265).
Keywords: Leadership